Characterization of 3d printed substrates for cell culture - Liew, Andy Wen Loong (2014)
Tissue engineering (TE) is a field of study which relies on engineering principles and life sciences in order to develop biocompatible structures (scaffolds) for the replacement, restoration, improvement, or assisted growth of human tissue. Implantable scaffolds provide a promising and alternative method to TE. Cells from the host can be cultured in-vitro onto the scaffolds and after sufficient proliferation and cell differentiation, the scaffold can then be implanted into bone defects or areas with damaged tissue allowing the target area to repair itself naturally. A common material used for these scaffolds is Hydroxyapatite (HA) because of its bioactivity and biocompatibility. One downside of pure HA is its weak mechanical properties, which limits its applications in hard tissue prosthetics. Alumina on the other hand is bio-inert, but it possesses far superior mechanical strength. This report investigates the compositional and bioactive properties of HA coated, 3D printed Alumina hybrid scaffolds for application in bone tissue engineering. Ceramic scaffolds made of bio-inert Alumina were fabricated via 3D printing. Scaffolds then underwent several processes of sintering, vacuum infiltration, and dip-coating with HA. TGA test was performed on the printed green part to evaluate the samples’ chemical compositions just after printing. Samples were also submerged in Simulated Bodily Fluid (SBF) for various amounts of time, allowing an Apatite layer to form naturally on the surface and within the pores of the scaffolds. FTIR and EDX was performed on these submerged samples to quantify and compare the elements found on each sample. SEM was used to visually quantify the amount of Apatite forming on each sample, as well as to evaluate the pore sizes present in the scaffolds. Finally, MSCs were culture onto SBF submerged samples to test for cell viability using the PrestoBlue® reagent.